Désiré - Borchard, Adolphe 1882-1967 (<<The>> Criterion collection, 2010)
"Sacha Guitry exchanges his usual top hat for a uniform in Désiré, playing a cavalier valet embroiled in an awkward flirtation with his new employer (played by the actor-director’s real-life wife, Jacqueline Delubac), who is involved with a stuffy politician. A carefree class farce filled with memorable supporting characters, Désiré blurs the distinction between upstairs and downstairs." [criterion.com]
Original: Frankreich 1937
Bildformat 1.33:1
Keywords: Film; DVD-Video